Hesperidin Prevents High Glucose-Induced Damage of Retinal Pigment Epithelial Cells - Liu, Wayne Young; Liou, Shorong-Shii; Hong, Tang-Yao; Liu, I-Min (Planta Medica, 2018)
The present study aimed to determine whether hesperidin, a plant-based active flavanone found in citrus fruits, can prevent high glucose-induced retinal pigment epithelial (RPE) cell impairment. Cultured human RPE cells (ARPE-19) were exposed to a normal glucose concentration (5.5 mM) for 4 d and then soaked in either normal (5.5 mM) or high (33.3 mM) concentrations of D-glucose with or without different concentrations of hesperidin (10, 20, or 40 µM) for another 48 h. The survival rates of the cells were measured using a 3-(4,5-dimethyl thiazol-2-yl)-2,5-diphenyl tetrazolium bromide reduction assay. With the help of a fluorescent probe, the intracellular production of reactive oxygen species (ROS) was evaluated. Colorimetric assay kits were used to assess the antioxidant enzyme activities, and western blotting was used to measure the expression of apoptosis-related protein. Hesperidin was effective in inhibiting high glucose-induced ROS production, preventing loss of cell viability, and promoting the endogenous antioxidant defense components, including glutathione peroxidase, superoxide dismutase, catalase, and glutathione, in a concentration-dependent manner. Furthermore, high glucose triggered cell apoptosis via the upregulation of caspase-9/3, enhancement of cytochrome c release into the cytosol, and subsequent interruption of the Bax/Bcl-2 balance. These detrimental effects were ameliorated by hesperidin in a concentration-dependent manner. We conclude that through the scavenging of ROS and modulation of the mitochondria-mediated apoptotic pathway, hesperidin may protect RPE cells from high glucose-induced injury and thus may be a candidate in preventing the visual impairment caused by diabetic retinopathy.
Keywords: hesperidin; high glucose; human retinal pigment epithelial cells; reactive oxygen species; apoptosis; diabetic retinopathy